Local and Systemic Immune Responses to Influenza A Virus Infection in Pneumonia and Encephalitis Mouse Models. (24th August 2017) - Nagaoka, Yoshiharu; Nosaka, Nobuyuki; Yamada, Mutsuko; Yashiro, Masato; Washio, Yosuke; Baba, Kenji; Morishima, Tsuneo; Tsukahara, Hirokazu
Abstract : Objective . To compare local and systemic profiles between different disease pathologies (pneumonia and encephalitis) induced by influenza A virus (IAV). Methods . An IAV pneumonia model was created by intranasal inoculation of C57BL/6 mice with influenza A/WSN/33 (H1N1) virus. Lung lavage and blood collection were performed on day 3 after IAV inoculation. Similarly, an IAV encephalitis mouse model was created by direct intracranial IAV inoculation. Cerebrospinal fluid (CSF) and blood collection were conducted according to the same schedule. Cytokine/chemokine profiles were produced for each collected sample. Then the data were compared visually using radar charts. Results . Serum cytokine profiles were similar in pneumonia and encephalitis models, but local responses between the bronchoalveolar lavage fluid (BALF) in the pneumonia model and CSF in the encephalitis model differed. Moreover, to varying degrees, the profiles of local cytokines/chemokines differed from those of serum in both the pneumonia and encephalitis models. Conclusion . Investigating local samples such as BALF and CSF is important for evaluating local immune responses, providing insight into pathology at the primary loci of infection. Serum data alone might be insufficient to elucidate local immune responses and might not enable clinicians to devise the most appropriate treatment strategies.